Variation in the expression of the first person of plural in texts of student elementary school: an pedagogical proposal - Cunha, Cátia Cilene Pereira Meireles; Silva, Maricineia Pereira Meireles da (Universidade Estadual Paulista, 2019)
The present work investigated the variants used for P4 expression in productions of Elementary II students. In the application of pedagogical mediation, focusing on the variation we /a gente, it was noticed that in texts of the genres experience report [+ orality] the students manifested the writing practice of the Brazilian literate society, alternating the use of we /a gente. In the report genre [+ literacy], the use of the traditional variant was semi-categorical. The results reflect, on the one hand, the deconstruction of the belief that writing only accepts the canonical variant and, on the other hand, the progress in the students' literacy process, because they have come to recognize the contexts in which the two variants of P4 can co-occur and those in which only the canonical variant is admitted, so that they have become able to move from one point to another of the continuum, depending on the textual genre in which the communicative event occurs.